Extreme Heat Resistance of Food Borne Pathogens Campylobacter jejuni, Escherichia coli, and Salmonella typhimurium on Chicken Breast Fillet during Cooking - Aarieke E.I. de Jong; Esther D. van Asselt; Marcel H. Zwietering; Maarten J. Nauta; Rob de Jonge (International Journal of Microbiology)
The aim of this research was to determine the decimal reduction times of bacteria present on chicken fillet in boiling water. The experiments were conducted with Campylobacter jejuni, Salmonella, and Escherichia coli. Whole chicken breast fillets were inoculated with the pathogens, stored overnight (4∘C), and subsequently cooked. The surface temperature reached 70∘C within 30 sec and 85∘C within one minute. Extremely high decimal reduction times of 1.90, 1.97, and 2.20 min were obtained for C. jejuni, E. coli, and S. typhimurium, respectively. Chicken meat and refrigerated storage before cooking enlarged the heat resistance of the food borne pathogens. Additionally, a high challenge temperature or fast heating rate contributed to the level of heat resistance. The data were used to assess the probability of illness (campylobacteriosis) due to consumption of chicken fillet as a function of cooking time. The data revealed that cooking time may be far more critical than previously assumed.